DINAMIKA KENDARAAN JALAN LURUS 3 PADA GEROBAK LISTRIK PENGANGKUT SAMPAH KAPASITAS 2 m3 - Edward Suhartono; G Soeharsono; Danardono Agus Sumarsono (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: A residential dump transport to a temporary garbage disposal medium using a human-powered dump cart is not humane. An electrical-powered propulsion system can be one of the eco-friendly system which can be implemented to the cart, thus substitutes the human’s role to do so. This propulsion is analyzed by using vehicle dynamic analysis. Vehicle dynamic analysis which is conducted, discuss tractive effort which overcomes resistances during vehicle’s movement and accelerates the vehicle, and specification of drive train, used to drive it. Based on analytical result, it is obtained an electric dump cart model which can move at a 25 km/h maximum velocity, 20° maximum inclination while it is empty loaded, and 10° maximum inclination while it is fully loaded.